Legal analysis of Judge's considerations in the decision of expiration of prosecution to be resolved legally in military discipline (Case Study Decision of the Main Military Court Number:27-K/PMU/BDG/AD/VI/2023) - John Hesekiel Simanjuntak (Goodwood Publishing, 2024)
Purpose: the author is interested in conducting this research; One of the problems related to the dilemma between formal or material categories can be seen related to the expiration date. Research methodology: This research is a normative legal research by discussing case studies of existing court decisions and is linked to applicable provisions and regulations and the opinions of legal scholars. Conclusions: The conclusion of this study is that the statute of limitations (verjaring) is regulated in Article 78 of the Criminal Code (KUHP) which is in fact the time limit for the public prosecutor to exercise his prosecution authority. In fact, the statute of limitations is a material aspect that is considered no longer needed for criminalization because it exceeds the time. However, there is an opinion that considers that the statute of limitations is a formal scope, because it is related to the administration of a case, not the main material of the case. On this basis, it can be seen that there are differences of opinion regarding the scope of the statute of limitations, which is in fact debated between the material or formal realm.